Systemic Inflammation Accelerates Changes in Microglial and Synaptic Markers in an Experimental Model of Chronic Neurodegeneration - Chouhan, Joe K.; Püntener, Ursula; Booth, Steven G.; Teeling, Jessica L. (Frontiers in Neuroscience, 2022)
Bacterial infections are a common cause of morbidity and mortality in the elderly, and particularly in individuals with a neurodegenerative disease. Experimental models of neurodegeneration have shown that LPS-induced systemic inflammation increases neuronal damage, a process thought to be mediated by activation of ‘primed’ microglia. The effects of a real systemic bacterial infection on the innate immune cells in the brain and neuronal networks are less well described, and therefore, in this study we investigated the alterations in microglia activation and phenotype and synaptic markers in response to a low grade, live bacterial infection. Mice with or without a pre-existing prion-induced neurodegenerative disease were given a single systemic injection of live Salmonella typhimurium at early (8 weeks) or mid-stage (12 weeks) of disease progression. Immune activation markers CD11b and MHCII and pro-inflammatory cytokines were analysed four weeks post-infection. Systemic infection with S. typhimurium resulted in an exaggerated inflammatory response when compared to ME7 prion mice treated with saline. These changes to inflammatory markers were most pronounced at mid-stage disease. Analysis of synaptic markers in ME7 prion mice revealed a significant reduction of genes that are associated with early response in synaptic plasticity, extracellular matrix structure and post-synaptic density, but no further reduction following systemic infection. In contrast, analysis of activity-related neuronal receptors involved in development of learning and memory, such as Grm1 and Grin2a, showed a significant decrease in response to systemic bacterial challenge. These changes were observed early in the disease progression and correlate with reduced burrowing activity. The exaggerated innate immune activation and altered expression of genes linked to synaptic plasticity may contribute to the onset and/or progression of neurodegeneration.